Dietary diversity, nutritional status, and agricultural commercialization: evidence from adult men of rural farm households - Olutosin Ademola Otekunrin; Idris Akanbi Ayinde; Rahman Akintayo Sanusi; Oluseye Olusegun Onabanjo (Elsevier, 2023)
Access to healthy and affordable diet hinged on the realization of Sustainable Development Goal 2, higher productivity and, economic prosperity while it is difficult for a poorly nourished people to achieve optimum production of goods and services. This study assessed whether dietary diversity (DD) and nutritional status of adult men are associated with crop commercialization index (CCI) levels of agricultural households in two states of Southwestern Nigeria. This research utilized 352 farm households, comprising 277 adult male members. The individual version of dietary diversity score (DDS) of 9 food groups was used to calculate adult men's DDS over a 24-h recall. Anthropometric data was obtained using body mass index (BMI) while CCI levels was estimated for each agricultural household. Logistic regression and ordered logit models were used to examine the determinants of adult men's dietary diversity and nutritional status respectively. Hundred percent of adult men consumed starchy staples, with 11.2% consuming egg, 5.8% milk and milk products and 0.4% consuming organ meat over 24-h recall. Adult men of CCI 2 and CCI 4 agricultural households recorded overweight prevalence of >20% in Ogun state while the association between DDS and CCI was statistically insignificant suggesting that being a member of any of the CCI households may not guarantee the consumption of healthy diets among adult men. From Logit regression analysis, it is more likely for adult men with higher farm size to attain the minimum DDS of 4 food groups than those with smaller size of farmland (OR = 4.78; 95% CI: 1.94, 11.76; p = 0.001). The age, farm experience, and cassava marketing experience were positively related to the likelihood of obtaining the minimum DDS. For adult men to achieve a healthy diet, their diet pattern must incorporate a more diversified intake of food from different food groups capable of improving their nutritional status. This study emphasized the need for relevant stakeholders to provide adequate nutrition knowledge intervention programmes capable of improving the diets and nutrition of adult men and other members of farm households.